Phase Change Material on Augmentation of Fresh Water Production Using Pyramid Solar Still - S. Ravishankara; P.K. Nagarajan; D. Vijayakumar; M.K. Jawahar (Center of Biomass & Renewable Energy (CBIORE), 2013)
The augmentation of fresh water and increase in the solar still efficiency of a triangular pyramid is added with phase change material (PCM) on the basin. Experimental studies were conducted and the effects of production of fresh water with and without PCM were investigated. Using paraffin as the PCM material, performance of the solar still were conducted on a hot, humid climate of Chennai (13°5′ 2